2018
DOI: 10.1177/1468796817751575
|View full text |Cite
|
Sign up to set email alerts
|

Multiculturalism, interculturalism, ‘multiculture’ and super-diversity: Of zombies, shadows and other ways of being

Abstract: Multiculturalism has increasingly become challenged and outcast, whether directly or summarily, as theoretically useful or empirically valid. This has come prominently from three corners: interculturalism, ‘everyday’ multiculturalism or ‘multiculture’ and super-diversity, in all of which the zombieness of multiculturalism is seen to be mutually reassured. Nevertheless, there are significant short comings that have not been thoroughly addressed and considered. In this article, I offer a thoroughgoing engagement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 105 publications
(122 reference statements)
0
25
0
Order By: Relevance
“…Although everyday multiculturalism has been critiqued for not adequately interacting with macro-level multiculturalism (Sealy 2018), this paper has shown that the macro-and micro-levels are closely linked through the incorporation of broader ideals and political discussions into micro-level encounters at the club. How multiculturalism is enacted at a micro-level is connected to national discourses on how we ought to share (semi)public spaces and what is expected of newcomers in terms of integration.…”
Section: Discussionmentioning
confidence: 95%
“…Although everyday multiculturalism has been critiqued for not adequately interacting with macro-level multiculturalism (Sealy 2018), this paper has shown that the macro-and micro-levels are closely linked through the incorporation of broader ideals and political discussions into micro-level encounters at the club. How multiculturalism is enacted at a micro-level is connected to national discourses on how we ought to share (semi)public spaces and what is expected of newcomers in terms of integration.…”
Section: Discussionmentioning
confidence: 95%
“…We are here not just thinking of those who self-define as interculturalists, but also those who invoke related concepts and vocabularies around the cosmopolitan society (Beck 2002), conviviality (Gilroy 2004), super-diversity (Vertovec 2007) and everyday multiculturalism (Wise and Velayutham 2009). These new discourses about diversity have played a similar, albeit not identical, role to those of the self-identified IC proponents (Padilla, Azevedo, and Olmos-Alcaraz 2015;Sealy 2018). A feature of these intellectual positions, most pronounced in IC, is an insistence that the nature of cultural diversity in urban centres has changed in the new millennium and, as a consequence, the flaws of MC are more evident than ever before.…”
Section: Multiculturalism and Interculturalismmentioning
confidence: 99%
“…Or as Karner and Parker (2011) articulated it when discussing an oft-derided area of already unloved Birmingham: conviviality becomes empirically distinctive only because it is always existing contiguously to the multiple conflicts routinely underpinned by the wider racial pathologization of minority residents. The point therefore, as far as I see it, is not that multiculture triumphs regardless, but that it endures and gets remade, releasing energies waiting to be harnessed by a less apologetic, less integrationist political programme that might command mass purchase (Sealy, 2018).…”
Section: The Locations Of Multiculturementioning
confidence: 99%